LLLT accelerates experimental wound healing under microgravity conditions via PI3K/AKT-CCR2 signal axis - Ye, Rongan; He, Yu; Ni, Wei; Zhang, Yiqiu; Zhu, Ying; Cao, Muqing; He, Ruida; Yao, Min (Frontiers in Bioengineering and Biotechnology, 2024)
Background and Purpose: The risk of skin injuries in space is increasing with longer space missions and a growing astronaut population. This highlights the importance of understanding the adverse effects of weightlessness on wound healing. The objective of this research was to examine the therapeutic potential of Low-Level Light Therapy (LLLT) on skin healing processes under simulated microgravity (SMG) conditions and uncover the underlying molecular mechanisms, thus providing innovative solutions and a sound theoretical basis for space skin injuries. Methods: Hindlimb unloading (HU) mice models were used to simulate weightlessness conditions, with or without a complete management of LLLT for 14 days. A systematic testing consisting of HE, Masson and immunohistochemical staining was performed against the standardized mouse tissue specimens. In vitro assessment of cellular biological functions under SMG conditions was carried out in the rotation system of culture (RSOC) using HaCaT and NIH3T3 cell-lines. Results: Under SMG conditions, LLLT significantly reduced skin wound area in HU mice, especially on Days 10 (P < 0.001), accompanied by increased collagen deposition and elevated levels of Ki67 and CD31. Moreover, LLLT showed impressive anti-inflammatory effects represented by the reduced in pro-inflammatory markers including LY6G, F4/80 and CD86, as well as the decreased levels of IL-1β, IL-6 and TNF-α. Conversely, an elevation in the anti-inflammatory marker CD206 was observed. By employing bioinformatics technology, we further found the PI3K/AKT signaling was prominent in the KEGG pathway analysis and CCR2 acted as a hub gene in the interaction network. Therefore, we demonstrated that LLLT could enhance the phosphorylation of PI3K/AKT and reduce CCR2 expression under SMG conditions, while CCR2 knockdown promoted the phosphorylation of PI3K/AKT, suggesting an important role of CCR2/PI3K/AKT signal axis in LLLT-accelerated wound healing under SMG conditions. Conclusion: LLLT induced activation of the PI3K/AKT signaling pathway through suppression of CCR2 expression, which significantly enhanced skin wound healing under SMG conditions.